Advancing Direct Payment Reforms in Ontario and Scotland - Sarah Carbone; Sara Allin (McMaster University Library Press, 2020)
Over the last several decades, there has been an increased interest in cash-for-care programs internationally. Important among these reforms has been the emergence of direct payments (DPs), which are cash payments given directly to individuals so that they can purchase their own community care services. In the mid-1990s, both Ontario and Scotland implemented early direct payment programs with the explicit goals of providing greater choice and control over social services to adults with disabilities. Since then, however, the programs have diverged considerably. In Scotland, negative public perceptions resulted in DPs conversion into a program option embedded within the Self-Directed Support program. In Ontario, DPs have never been required by law and have instead expanded through multiple distinct programs funded through different government ministries. This paper compares the evolution of DPs in these two jurisdictions in order to better understand the actors and mechanisms that contributed to this divergence. Using the 3-I framework, we explore the ideas, interests and institutions that have shaped these reforms into their current structures. Our analysis offers several insights for other jurisdictions considering expanding direct payment reforms. These include recognizing: 1) policy conversion as a tool for managing negative perceptions of a reform, 2) policy levers for encouraging compliance among administering authorities, 3) divisions between health and social care as limiting possible expansion of the reform, and 4) program evaluations as justification for the reform's expansion. Les programmes de chèques services suscitent un intérêt croissant dans le monde depuis quelques décennies. Au nombre de ces réformes, une tendance importante a été l'émergence de paiements directs, qui sont des paiements en espèces versés directement aux bénéficiaires pour qu'ils achètent eux-mêmes leurs services de soins communautaires. Au milieu des années 1990, l'Ontario et l'Écosse ont tous deux mis en place de tels programmes de manière pionnière, avec comme but explicite d'offrir plus de choix et de contrôle sur les services sociaux aux adultes handicapés. Depuis, cependant, ces deux programmes ont divergé considérablement. En Écosse, une réaction négative de l'opinion publique à conduit à transformer les paiements directs en une option au sein du programme Self-Directed Support (soutien auto-administré). En Ontario, les paiements directs n'ont jamais été mis en place légalement et se sont développés à travers divers programmes financés par des ministères différents. Cet article compare l'évolution des paiements directs dans ces deux entités politiques afin de mieux comprendre les acteurs et les mécanismes ayant contribué à cette divergence. Suivant le concept 3-I, nous explorons les idées, les intérêts et les institutions ayant façonné ces réformes dans leur état actuel. Notre analyse fournit des indications aux autres entités tentées par des réformes de paiements directs, entre autres : 1) la conversion de politique comme un outil de gestion des perceptions négatives d'une réforme, 2) les leviers politiques pour améliorer l'adhésion des autorités administrative, 3) les limites potentiellement apportées à la réforme par la séparation entre le sanitaire et le social et, 4)  les évaluations de programmes comme une justification de l'expansion de la réforme.